A full-spectrum k-distribution look-up table for radiative transfer in nonhomogeneous gaseous media. (January 2016) - Wang, Chaojun; Ge, Wenjun; Modest, Michael F.; He, Boshu
Abstract: A full-spectrum k -distribution (FSK) look-up table has been constructed for gas mixtures within a certain range of thermodynamic states for three species, i.e., CO2, H2 O and CO. The k -distribution of a mixture is assembled directly from the summation of the linear absorption coefficients of three species. The systematic approach to generate the table, including the generation of the pressure-based absorption coefficient and the generation of the k -distribution, is discussed. To efficiently obtain accurate k -values for arbitrary thermodynamic states from tabulated values, a 6-D linear interpolation method is employed. A large number of radiative heat transfer calculations have been carried out to test the accuracy of the FSK look-up table. Results show that, using the FSK look-up table can provide excellent accuracy compared to the exact results. Without the time-consuming process of assembling k -distribution from individual species plus mixing, using the FSK look-up table can save considerable computational cost. To evaluate the accuracy as well as the efficiency of the FSK look-up table, radiative heat transfer via a scaled Sandia D Flame is calculated to compare the CPU execution time using the FSK method based on the narrow-band database, correlations, and the look-up table. Results show that the FSK look-up table can provide a computationally cheap alternative without much sacrifice in accuracy. Highlights: A full-spectrum k -distribution look-up table is constructed for gas mixtures. A large range of thermodynamic states for CO2 H2 O and CO, is included. The systematic approach to generate the FSK look-up table is discussed. Both accuracy and efficiency of the FSK look-up table are investigated.